Uma leitura psicanalítica de um caso de histeria feminina - Gomes, Francielle Gonzalez Correia (2009)
The present study concerns a clinical case comprehended as female hysteria. Its objectives are the identification of vicissitudes placed during the psychosexual development of a former patient which facilitated her hysterical constitution and the enlightening of the unconscious contents of her behaviors and symptoms that help clarifying such constitution. This dissertation is based, mainly, in freudian psychoanalysis and Piera Aulagnier s theoretical contributions to the subject. The work contemplates feminine psychosexual constitution, hysteria s psychopathological constitution and the analysis of a clinical case whose prevailing symptomatic manifestations point to anxiety hysteria. Depressive and aggressive behaviors of the patient s father are pointed as factors that contributed to her hysterical constitution. Concerning the aspects that indicate hysterical organization, are emphasized: childishness, dependence on objects; self disqualification conducts alternating with arrogance; exacerbation and identification with the beloved object; the narcissistic object choice; apparent overlap between sexual and incestuous relationships; repression of adult sexuality and unawareness of what is desirable in a woman